WELCOME HOME? PARENTS’ AND TEACHERS’ EXPERIENCES EDUCATING RETURNEES’ CHILDREN IN LITHUANIA - Budginaitė, Irma; Mašidlauskaitė, Rūta (Politologija, 2015)
The article is based on a research project funded by the Lithuanian Research Council and conducted in Lithuania, with a focus on the challenges when integrating children that are coming back with parents from abroad into the Lithuanian education system. It is based on semi-structured interviews and one focus group with teachers that have experience educating returnees’ children as well as interviews with return migrants that have children under eighteen. In addition, two representative surveys – the Lithuanian population survey and the survey of return migrants – are used to illustrate the tendencies of return migration. This article aims to contribute to the development of return migration research field and raises such questions as: How the educational opportunities for children make impact on decision to return to Lithuania? How educational institutions are chosen and how the pupils’ knowledge is evaluated? What are the main challenges that teachers face while educating returnees’ children? The research has revealed that family circumstances are one of the most important factors motivating emigrants to return. The desire to start a family and raise children in a Lithuanian cultural environment and children’s education may be important aspects when deciding to return. Parents that are planning to return are interested in educational opportunities for children, are collecting relevant information and, if possible, are visiting schools before returning to Lithuania. Some of them express their worries about the preparation of teachers to educate their children. The research also shows that not all teachers are aware how to deal with the challenges they face educating pupils with the migrant background. The qualitative interviews have revealed that it is harder to get relevant information for teachers from small towns, and it is hardly possible for them to participate in the trainings that are organised in the cities. Therefore, teachers are obliged to find individual creative solutions for teaching children. According to the interviewees, such measures as individualised course materials, specific training courses, allocation of additional funding for the Lithuanian language or other subject classes could contribute to a better integration of returnees’ children. The interviews also disclosed that not all policy measures for the integration of children with the migrant background are applicable in small towns.